Development of Customer Loyalty in Alternative Tourism Context (Laisvalaikio tyrimai, 2018)
Research background. Global trends in the development of tourism are increasingly focused on being environmentally friendly, reflecting on the principles of sustainable development, the search for new forms of tourism, which would not be mass character and provide other cognitive and travel perspectives. One of those opportunities is alternative tourism development. In response to changes in the tourism sector the European Union is pleased to support the alternative tourism – tourist area that is developing rapidly, accommodating the strongest advantages – the region’s natural diversity and rich cultural resources (Kinderis, 2010). One of the most notable changes in this day in the alternative tourism is becoming a new form of tourism. Dark tourism as a branch of alternative tourism was examined by the foreign authors (Lennon, Foley, 2000; Kendle, 2008; Stone, Sharpley, 2008). The aim of the research was to investigate the development of customer loyalty in alternative tourism areas/objects. Scientific problem question. Is it possible to form customer loyalty in the alternative tourism context? To achieve the target, we set four tasks: to review the concept of alternative tourism; analyse the genesis of dark tourism; explore the concept of customer loyalty; identify customer loyalty formation stages. Methods: scientific literature analysis, questionnaire survey, descriptive statistical analysis (SPSS 17.0.). Results. Study results show that after a visit to dark tourism sites/objects, respondents understood the value created and named a motivational factor – what is important in the formation of loyalty. After the visit, respondents perceived site/object and time better (75%); were surprised by the strength and endurance of the people (71%); got a lot of useful information (69%). Respondents questioned what motivated them to visit dark tourism site/object, the mostly mentioned curiosity and desire to learn more (86%); desire to visit yet not visited area (84%); the quest of knowledge (68%); new impressions and experience of the quest (58%); nostalgia, the desire to understand the past (52%). The study also made clear that the respondents fulfilled their expectations (66%) and received what they expected (65%), which are the one of loyalty formation stages (Navickienė, 2010). Almost half of the respondents (43%) remembered only the good things after a visit, and as many as 70% of tourists would recommend dark tourism sites / objects to their friends or relatives. Conclusions. In particular, dark tourism caused mystical and sympathizing feelings to people. There are five basic emotions that interact with the psychological status of “dark tourists”: amazement, curiosity, fear, pity and sadness. The main motivation factors for the choice of dark tourism products are educational and emotional, i.e. the desire to feel connected with heritage.Keywords: customer loyalty, alternative tourism, dark tourism.